Potensi Logam Tanah Jarang (LTJ) pada Parting Batubara dan Estimasi Sumberdaya Hipotetik di PT Kuansing Inti Makmur: Potential of Rare Earth Elements in Coal Parting and Hypothetical Resource Estimation at PT Kuansing Inti Makmur - Putri Abby Larassati; Muhammad Ikrar Lagowa; Yudi Arista Yulanda (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2026)
Rare Earth Elements (REEs) have become critical components in modern technology; however, global reliance on Chinese supply (>80%) and the scarcity of economic deposits necessitate the diversification of REE sources, including utilizing coal ash. This study examines the REE potential in coal parting as the primary source of coal combustion ash materials at PT Kuansing Inti Makmur (PT KIM), Bungo Regency, Jambi Province, which features multi-parting coal characteristics with a high ash content (14.36%). The methodology includes Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES) analysis for REE quantification and petrographic analysis for mineralogical characterization. The results reveal that the total REE content in the parting reaches 180.01 ppm, dominated by Cerium (Ce) (65.68 ppm) and Neodymium (Nd) (38.91 ppm). Petrographic analysis identifies the REE-bearing host rock as siliciclastic sediment composed primarily of quartz and feldspar within a clay matrix. Based on a parting volume of 85,000 m3, the hypothetical resource estimation yields a total potential of 32.13 tonnes of REE, including Ce (11.7 tonnes) and Nd (6.9 tonnes). These findings indicate that the high-ash, multi-parting coal parting at PT KIM holds significant potential as an alternative REE source through the utilization of residual coal combustion ash. The presence of REE within the parting enables its accumulation and enrichment during the combustion process.